INCORPORATING ICTs INTO TEACHING PRIMARY SCHOOL PUPILS ENGLISH LANGUAGE PRODUCTIVE SKILLS IN BUDUDA DISTRICT - ABONG EVA (My University, 2024)
Abstract The history of English language teaching (ELT) is a fascinating journey that has evolved significantly over time (Classical Method 17th-19th centuries). During this period, foreign language learning was primarily associated with Latin and Greek. The focus was on grammatical rules, syntactic structures, vocabulary memorization, and translation of literary texts. Oral communication in the language under study was not emphasized. The Classical Method later transformed into the Grammar Translation Method, which remains popular even today. Unfortunately, it prioritized dissecting language into grammar components rather than fostering communicative abilities (Thanasoulas, 2020). According to Francois Gouin’s experiences, learning German led to insights into language teaching (The Direct Method: Late 19th Century). He advocated for direct interaction with the language, emphasizing oral communication. The Direct Method aimed to teach language through conversation, immersion, and context, rather than relying solely on grammar rules. It marked a shift towards practical language use and communication skills (Thanasoulas, 2020). The 20th century witnessed significant changes in ELT. There was introduction of Audio-lingual Method, which focused on repetition, drills, and mimicry to develop speaking and listening skills. Additionally, Communicative Approach that emphasized real-life communication, interactive activities, and functional language use. More, Task-Based Learning in which learners engage in meaningful tasks to acquire language naturally. Finally, Technology Integration where the introudction of computers, multimedia, and online resources transformed language learning (Thanasoulas, 2020).